2014
DOI: 10.1007/s12640-014-9467-y
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and Antioxidative Effect of Ibuprofen in the Rotenone Model of Parkinson’s Disease

Abstract: Idiopathic Parkinson's disease is a neurodegenerative disorder that affects approximately 1 % of the population over 55 years of age. The disease manifests itself through motor and nonmotor symptoms induced mainly by the neurodegeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc). The possible mechanisms involved in this pathology include mitochondrial dysfunction, neuroinflammation, and oxidative stress. The present study evaluated the effects of the nonselective cyclooxygenase inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 63 publications
1
24
0
1
Order By: Relevance
“…It must be noted that ibuprofen demonstrated the most significant antioxidant effect. Previously minor data demonstrated that this anti-inflammatory drug can exercise antioxidant properties predominantly through the COX inhibition (Milatovic et al, 2011; Zaminelli et al, 2014). However, this mechanism is absented in flies.…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that ibuprofen demonstrated the most significant antioxidant effect. Previously minor data demonstrated that this anti-inflammatory drug can exercise antioxidant properties predominantly through the COX inhibition (Milatovic et al, 2011; Zaminelli et al, 2014). However, this mechanism is absented in flies.…”
Section: Discussionmentioning
confidence: 99%
“…Some repositioning hits for MDD-CONVERGE included oxotremorine-M, a muscarinic acetylcholine receptor agonist that may ameliorate depressive symptoms and restore hippocampal neurogenesis in an animal model 51 and capeserod, a 5-HT4 receptor agonist shown effective in a mouse model 52 . For MDD-PGC, top-listed drugs include three NSAIDs, namely ibuprofen, meclofenamate and flufenamic acid, which possess anti-inflammatory actions that may also be beneficial for depression 53,54 . Remarkably, our analysis recovered a known augmentation therapy for depression, namely Cytomel (or synthetic triiodothyronine [T3]) 55 .…”
Section: Based On Gene-sets Derived From Pubchem and Chemblmentioning
confidence: 99%
“…P<0.05 was considered to indicate a statistically significant difference. 3 -induced neurotoxicity mouse model. In order to analyze the pharmacological effects of ibuprofen on the learning and memory abilities of AlCl 3 -treated mice, ibuprofen (100 mg/kg/day) and AlCl 3 (150 mg/kg/day) were administered to the appropriate groups for 12 days, after which the mice were subjected to memory testing using the Morris water maze test for the final 7 days of treatment, prior to sacrifice.…”
Section: Open Field Testmentioning
confidence: 99%